The effect of helminth infection on vaccine responses in humans and animal models: A systematic review and meta-analysis - Natukunda, Agnes; Zirimenya, Ludoviko; Nassuuna, Jacent; Nkurunungi, Gyaviira; Elliott, Alison M.; Webb, Emily L. (Parasite Immunology, 2022)
Vaccination has potential to eliminate infectious diseases. However, parasitic infections such as helminths may hinder vaccines from providing optimal protection. We reviewed existing literature on the effects of helminth infections and their treatment on vaccine responses in humans and animals. We searched literature until 31 January 2022 in Medline, EMBASE, Global health, Scopus, and Web of science; search terms included WHO licensed vaccines and human helminth types. Standardized mean differences (SMD) in vaccine responses between helminth infected and uninfected or anthelminthic treated and untreated individuals were obtained from each study with suitable data for meta-analysis, and combined using a random effects model. Analysis was stratified by whether helminth exposure was direct or prenatal and by vaccine type. This study is registered with PROSPERO (CRD42019123074). Of the 4402 articles identified, 37 were included in the review of human studies and 24 for animal experiments. For human studies, regardless of vaccine type, overall SMD for helminth uninfected/treated, compared to infected/untreated, was 0.56 (95% CI 0.04–1.07 and I2 = 93.5%) for direct helminth exposure and 0.01 (95% CI −0.04 to 0.07 and I2 = 85.9%) for prenatal helminth exposure. Effects of anthelminthic treatment were inconsistent, with no overall benefit shown. Results differed by vaccine type, with responses to live vaccines most affected by helminth exposure. For animal studies, the most affected vaccine was BCG. This result indicates that helminth-associated impairment of vaccine responses is more severe for direct, than for prenatal, helminth exposure. Further research is needed to ascertain whether deworming of individuals before vaccination may help improve responses.